Hydatid Cyst Diagnosed by Endoscopic Ultrasound - F. Castro-Poças; Tarcísio Araújo; André Coelho; Donzilia Silva; Isabel Pedroto (Canadian Journal of Gastroenterology and Hepatology)
A 69-year-old female with unremarkable past history underwent endoscopy for dyspepsia. She denied weight loss or anorexia. Upper endoscopy revealed a bulge in the lesser curvature and posterior wall of the stomach with 4-5 cm. Endoscopic ultrasound was performed which showed a heterogeneous lesion, anechogenic in the major part, with a floating membrane inside, the greatest diameter of 90.8 × 17.2 mm, originated in the left liver lobe. Surgical resection was performed. Pathologic examination revealed a cystic lesion with an acellular thick fibrous wall, surrounded by a conspicuous inflammatory reaction. The cyst wall revealed a characteristic lamellar pattern of the fibers. In the internal surface of the lesion, there were remains of membranous structures, amidst which a vestigial Protoscolex was noted. In the presented case, a floating membrane was observed, which is a pathognomonic feature, establishing the diagnosis of hydatid cyst type 3. Fine needle aspiration guided by ultrasound was not performed due to the certainty in the diagnosis. To the authors’ knowledge, these are the first images by endoscopic ultrasound of hydatid cyst of liver presented as a bulge in the stomach with pathognomonic features, which allowed the definitive diagnosis with no need for further diagnostic tests.